Isolated tubal metastasis from an incidental HPV-associated endocervical adenocarcinoma presented as an adnexal mass: A case report - Hessa Aljhdali; Janos Balega; Anthony Williams; Raji Ganesan (Elsevier, 2023)
Tubal metastasis from endocervical adenocarcinoma is uncommon and is discovered as an incidental finding on routine sampling of fallopian tubes. In this paper, we present the case of an 81-year-old woman who presented with an adnexal mass during investigations of postmenopausal bleeding. Hysterectomy and bilateral salpingo-oophorectomy with excision of the left adnexal mass were performed, which led to the diagnosis of an incidental HPV-associated endocervical adenocarcinoma with secondary, macroscopic tubal involvement. The patient received adjuvant pelvic radiotherapy and remained well after three months of follow-up, with no evidence of recurrence. Only a few cases of endocervical adenocarcinoma with tubal metastasis have been reported in the literature, which are commonly associated with ovarian, uterine corpus, and/or parametrial tissue involvement. To date, there are only two reported cases of isolated tubal metastasis, and in both cases, tubal involvement was discovered microscopically. Data on the impact of secondary tubal involvement on patient outcomes are limited.